Subjugation of Women in Anita Nair’s Mistress: A Study on Eco-Feminism - Katuwal, Saraswati (Research Nepal Journal of Development Studies, 2021)
The condition of Nepalese or Indian women still in the primitive stage from a modern eco-feminism perspective. The socio-cultural status of a woman of developing economies like Nepal and India, Anita Nair’s Mistress provides a clear spectrum. The pain, suffocation, suppression, passion, love, and hate are beautifully analyzed in the Novel. To find out its relevancy in the present context of ecofeminism the study has adopted the textual analysis method with selected literature presented in reference. The researcher tried to find the Subjugation, through Anita Nair’s Mistress focuses on the Subjugation of females, and how they face extremity in a male-dominated society. The study explores the resistance, struggle of women in this context of what women are for the male and hence how they are treated as per the Novel – Mistress by Anita Nair.